What Do Placebo and Nocebo Effects Have to Do With Health Equity? The Hidden Toll of Nocebo Effects on Racial and Ethnic Minority Patients in Clinical Care - Yetman, Hailey E.; Cox, Nevada; Adler, Shelley R.; Hall, Kathryn T.; Stone, Valerie E. (Frontiers in Psychology, 2021)
A placebo effect is a positive clinical response to non-specific elements of treatment with a sham or inert replica of a drug, device, or surgical intervention. There is considerable evidence that placebo effects are driven by expectation of benefit from the intervention. Expectation is shaped by a patient’s past experience, observations of the experience of others and written, verbal or non-verbal information communicated during treatment. Not surprisingly, expectation in the clinical setting is strongly influenced by the attitude, affect, and communication content and style of the healthcare provider. While positive expectations produce beneficial effects, negative information and experiences can lead to negative expectations and consequently negative or nocebo effects. Hence, both the absence of placebo and presence of nocebo effects can reduce the quality of clinical care. Key components identified and studied in the placebo and nocebo literature intersect with factors identified as barriers to care for Black patients, including poor patient-physician communication, medical mistrust, and perceived discrimination. Thus, in the context of discrimination and bias, the absence of placebo and presence of nocebo-generating influences in clinical settings could reinforce racial and ethnic inequities in clinical outcomes and care. These inequities have consequences that ripple through the medical system, strengthening adverse short- and long-term outcomes. Here, we propose that nocebo and placebo mechanisms may play a role in exacerbation of negative outcomes related to unequal treatment in the clinical encounter.